Multiple Hydrogen Bonding Enables the Self‐Healing of Sensors for Human–Machine Interactions. (14th June 2017) - Cao, Jie; Lu, Canhui; Zhuang, Jian; Liu, Manxiao; Zhang, Xinxing; Yu, Yanmei; Tao, Qingchuan
Abstract: Despite its widespread use in signal collection, flexible sensors have been rarely used in human–machine interactions owing to its indistinguishable signal, poor reliability, and poor stability when inflicted with unavoidable scratches and/or mechanical cuts. A highly sensitive and self‐healing sensor enabled by multiple hydrogen bonding network and nanostructured conductive network is demonstrated. The nanostructured supramolecular sensor displays extremely fast (ca. 15 s) and repeatable self‐healing ability with high healing efficiency (93 % after the third healing process). It can precisely detect tiny human motions, demonstrating highly distinguishable and reliable signals even after cutting–healing and bending over 20 000 cycles. Furthermore, a human–machine interaction system is integrated to develop a facial expression control system and an electronic larynx, aiming to control the robot to assist the patient's daily life and help the mute to realize real‐time speaking.